THE MECHANISM OF HOLE TRANSPORT IN PHOTOCELLS BASED ON a-Si: H. - S. Zaynobidinov; U. Babakhodzhayev; A. Nabiyev (American Journals Publishing, 2023)
Investigate the hole transfer mechanism in a-Si:H films using photovoltage characteristics (photo-CVCH) of a vidicon target.Theoretically obtained, if the concentration of photogenerated injected holes exceeds the concentration of defective states, then in the a-Si: H mobility gap in photo-CVCH, a portion is observed that obeys the quadratic law (I ~ U2). It was explained that in order to obtain reliable information from this section on the hole transport mechanism, it is necessary to take into account changes in the a-Si: H dielectric constant and hole lifetime depending on the applied voltage.
Keywords: Amorphous hydrogenated silicon, vidicon target, hole trap, energy positions of traps, mobility gap, sticking centers.